PERAN MODAL SOSIAL DALAM PELESTARIAN TANAMAN MANGROVE DI DESA TONGKE-TONGKE KECAMATAN SINJAI TIMUR - Raisa, Daeva Mubarika; Asrul, Asrul; Winadia, Winadia; Salmiati R, Salmiati; Nursinar, Nursinar (Jurnal Riset Multidisiplin Agrisosco, 2024)
This research was conducted with the aim of examining the role of social capital in preserving mangrove plants in Tongke Tongke Village, East Sinjai District, Sinjai Regency. This research uses a qualitative descriptive research method with data collection techniques using observation, interviews, and questionnaires. The results of this research show that there are three important indicators in the application of social capital, namely trust, norms, and networking. The application of social capital is considered important for the people of Tongke Tongke Village because the application of trust indicators can form social interactions that can last for a long time, and the application of norms can help the community comply with the rules in managing mangrove forests as a source of life and the existence of a network built by the Tongke Tongke Village government. both internal and external help in preserving mangrove forests which must be maintained by all parties, both government and community. The condition of the mangrove forests in Tongke - Tongke Village, East Sinjai District requires effective forest rehabilitation and integrated management. In integrated mangrove forest management, the role of each stakeholder involved in the management is very necessary. Mangrove forest management in Tongke - Tongke Village involves local communities and the condition of the mangrove forests in the village is starting to improve and some are still experiencing damage, this cannot be separated from the social capital of the local community who manage and utilize the mangrove forests.